Do antiviral CD8+ T cells select hepatitis C virus escape mutants? Analysis in diverse epitopes targeted by human intrahepatic CD8+ T lymphocytes. - Komatsu, H; Lauer, G; Pybus, O; Ouchi, K; Wong, D; Ward, S; Walker, B; Klenerman, P (2006)
Hepatitis C virus (HCV) is a variable RNA virus that can readily establish persistent infection. Cellular immune responses are important in the early control of the virus. Evidence from animal models suggests that mutation in epitopes recognized by CD8+ T lymphocytes may play an important role in the establishment of persistence but in human persistent infection, equivalent evidence is lacking. We investigated this by analysing a unique resource: viruses from a set of chronically HCV-infected individuals in whom the CD8+ T-cell responses in liver had previously been accurately mapped. Virus was sequenced in seven individuals at 10 epitopes restricted by 10 human leucocyte antigen (HLA) molecules. Two main patterns emerged: in the majority of epitopes sequenced, no variation was seen. In three epitopes, mutations were identified which were compatible with immune escape as assessed using phylogenetic and/or functional studies. These data suggest that - even where specific intrahepatic T cells are detectable - many epitopes do not undergo mutation in chronic human infection. On the contrary, virus may escape from intrahepatic CD8+ T-cell responses in a 'patchy' manner in certain specific epitopes. Furthermore, longitudinal studies to identify the differences between 'selecting' and 'nonselecting' intrahepatic CD8+ T-cell responses are needed in HCV infection.